The effect of locally based and imported lick stones on the growth and economic productivity of African dwarf sheep during the dry season in Benin - DOKUI, Faustin; BABATOUNDE, SÉVÉRIN; HOUNDONOUGBO, M. FRÉDÉRIC; AMOULE, Fiacre EMMANUEL; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI (My University, 2023)
Objective: This study aimed to make and compare the effects and economic viability of lick stones based on local feedstuffs and imported ones. Materials and Methods: Two-lick stones (minerals and multi-nutritional) based on local feedstuffs were made. An imported lick stone (ILS) was purchased at a local market. Four dietary treatments (the three different lick stones and a control group) were established, with six dwarf sheep receiving each treatment. The experiment was carried out over 90 days. Growth and economic parameters were calculated and compared. Results: The feed intake of sheep in the multi-nutritional lick stone group was better than that of the other groups. The feed conversion ratio was best for the lick stones made with local feedstuffs. The economic return (economic feed efficiency) was best for the mineral lick stone. For a unit of money invested in the feed supplements, the sheep fed with lick stone based on local feedstuffs have been allowed to gain 100.21 basic monetary unit of some West African countries more than the ones fed with imported feeds (p < 0.05). Conclusion: It is not desirable to use ILS because the economic and growth performance of sheep fed with the ILS was even lower than that of the non-supplemented sheep.
Keywords: African dwarf sheep; body weight; gain; dry season; economic return; lick; stone supplementation